2018
DOI: 10.1111/imcb.12018
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αM activation and upregulation on esophageal eosinophils and periostin‐mediated eosinophil survival in eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is an increasingly recognized allergic disease associated with dysphagia and esophageal fibrosis. We aimed to determine expression patterns of specific eosinophil integrins that promote eosinophilic infiltration of the esophageal epithelium, and to determine how key EoE-related cytokines influence eosinophil activation and survival. Esophageal and peripheral eosinophils were isolated from 20 adult subjects with EoE for immunophenotyping and integrin profiling using multicolor flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
(94 reference statements)
2
12
0
Order By: Relevance
“…18 This observation is in congruence with the recent finding that the migration of peripheral eosinophils to the esophagus and their survival in situ are linked to the up-regulation and conformational change of αMβ2, also known as CD11b/CD18, integrin, and its interaction with periostin, which is also highly expressed in EoE. 19,20 Treatment with budesonide for 12 weeks, or as for as short a period as 15 days, has been shown to achieve histologic, endoscopic, and clinical improvement in adolescent to adult EoE patients. 21,22 Budesonide treatment in adult EoE patients reduces esophageal eosinophil density, absolute peripheral eosinophilia, and serum levels of CCL17, CCL18, CCL26, eosinophil-cationic protein, and mast cell tryptase.…”
Section: Topical Corticosteroidssupporting
confidence: 76%
“…18 This observation is in congruence with the recent finding that the migration of peripheral eosinophils to the esophagus and their survival in situ are linked to the up-regulation and conformational change of αMβ2, also known as CD11b/CD18, integrin, and its interaction with periostin, which is also highly expressed in EoE. 19,20 Treatment with budesonide for 12 weeks, or as for as short a period as 15 days, has been shown to achieve histologic, endoscopic, and clinical improvement in adolescent to adult EoE patients. 21,22 Budesonide treatment in adult EoE patients reduces esophageal eosinophil density, absolute peripheral eosinophilia, and serum levels of CCL17, CCL18, CCL26, eosinophil-cationic protein, and mast cell tryptase.…”
Section: Topical Corticosteroidssupporting
confidence: 76%
“…Blood eosinophils are broadly identified by flow cytometry as SSC hi SiglecF/8 + CD62L + CCR3 + IL5Rα + leukocytes (reviewed in [4]), and express surface integrins including α L β 2 (CD11a/CD18), α M β 2 (CD11b/CD18d), α D β 2 (CD11d/CD18), α6 (CD49f), α 4 β 7 (CD49d/β 7 ), and β 1 (CD29) integrins (e.g., α 4 β 1 ) in low-activation conformations in the steady state [38,39]. Whether systemic signals within the context of eosinophilic inflammatory diseases may temporarily modulate surface receptors on circulating eosinophils, including integrin expression, activation markers and growth factor receptors, is an area of active current research, with most progress to date coming from studies in asthmatics.…”
Section: Blood Eosinophilsmentioning
confidence: 99%
“…Akin to eosinophils recruited to asthmatic airways, Vimilathas et al demonstrated increased expression of total high-activity conformation αM (CD11b) integrin on esophageal eosinophils from EoE patients, expression of which promoted eosinophil survival through interactions with periostin [38]. Ultrastructural studies demonstrate esophageal tissue eosinophils undergo distinct modes of secretion (i.e., piecemeal degranulation versus cytolysis), the latter presumably indicative of pro-inflammatory functions, in patients with EoE [66].…”
Section: Phenotypic Heterogeneity In Disease-associated Microenvironmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since eosinophils also bear α4β7 integrins and can bind to vascular endothelial MAdCAM-1, vedolizumab may be useful in EGIDs by directly inhibiting eosinophil intestinal homing [9]. Moreover, since Th2-derived cytokines Fig.…”
Section: Vedolizumab Mechanisms In the Gi Tractmentioning
confidence: 99%